SYNTHESIS AND CHARACTERIZATION OF MATERIALS MACROPOROUS MODIFIED SILICON OXIDE - Osorio A., Ana (2007)
The present study has as main objecuve the search of new materials, among them the porous materials whose diversity of pore diameter confers lO the same specific properties, those that in turn determine a series of applications like adsorbents. catalysts, and shield materials, among others. The investigatíon consists of the synthes1s of macroporous materials by the method Sol-Gel, using reactive of low cost as sodium silicate (silicon source) and includes/understanos the following stages: 1) control of hydrolysis of the inorganic precursors: 2) formatíon oí the rnacrostructure material (hydrothermal synthesis) and 3) elimination of the organic matter by calcinations. The structural characterization and the degree of crystalinidad were made by means of Diffraction of Rays-X (DRX) and Electronic Diffraction of Area Selecta.(DEAS), whereas the morphologic analysis was made through an Electronic Microscopy of Transmission (MET), being observed the macrospores forrnation with 100 nm of diameter.